2018
DOI: 10.1051/mfreview/2018008
|View full text |Cite
|
Sign up to set email alerts
|

A review on the modeling and simulations of solid-state diffusional phase transformations in metals and alloys

Abstract: Solid-state diffusional phase transformations are vital approaches for controlling of the material microstructure and thus tailoring the properties of metals and alloys. To exploit this mean to a full extent, much effort is paid on the reliable and efficient modeling and simulation of the phase transformations. This work gives an overview of the developments in theoretical research of solid-state diffusional phase transformations and the current status of various numerical simulation techniques such as empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 148 publications
(173 reference statements)
0
16
0
Order By: Relevance
“…Phase transformations are induced by driving forces and controlled by the diffusivities of the relevant species. [ 37 ] In this study, the as‐solidified material consists solely of the γ phase. In thermodynamic equilibrium, CMSX‐4 consists of roughly 70 % γ′ phase embedded in the γ matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Phase transformations are induced by driving forces and controlled by the diffusivities of the relevant species. [ 37 ] In this study, the as‐solidified material consists solely of the γ phase. In thermodynamic equilibrium, CMSX‐4 consists of roughly 70 % γ′ phase embedded in the γ matrix.…”
Section: Discussionmentioning
confidence: 99%
“…4a). Solid-state diffusional phase transformation, which includes nucleation, growth, and impingement, is directly responsible for the arrangements of constituent composites, which include a specific volume fraction of spatially distributed phases with various compositions, grain size and morphology with random orientation, and their spatial distribution [20]. Numerical simulation approaches may be employed, in future scope of the current work, to account for experimental condition limitations and dynamically recreate microstructure development.…”
Section: Sem and Edxmentioning
confidence: 99%
“…Numerical simulation approaches may be employed, in future scope of the current work, to account for experimental condition limitations and dynamically recreate microstructure development. Empirical and analytical models [20], phase-field models [21,22], cellular automaton models, Monte Carlo models, and molecular dynamics approaches [20] are now the most sophisticated numerical simulation methods. In general, empirical and analytical models provide more average information, such as average grain size and phase volume fraction of microstructure development at the macroscale.…”
Section: Sem and Edxmentioning
confidence: 99%
“…Among many published PF papers those dedicated to phase transformations should be mentioned (Rudnizki et al, 2011;Steinbach & Apel, 2006). Recently published research focus on the 3D solution (Bollada et al, 2015) and multi PF approach (see Mecozzi et al, 2016;Liu et al, 2018). Good review of the FP models can be also found in the book by Choudhury (2013).…”
Section: Full Field Modelsmentioning
confidence: 99%
“…A review of the full field models of diffusional phase transformations including CA, MC and MD methods is presented by Liu et al (2018). A thorough comparative discussion of the mean field and full field approaches to modelling dynamic recrystallization is presented in the Maire's PhD thesis (2018).…”
Section: Full Field Modelsmentioning
confidence: 99%